2004
DOI: 10.1097/01.ju.0000101622.74236.94
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin is Highly Over Expressed in and a New Candidate for a Prognostic Indicator in Prostate Cancer

Abstract: Purpose: Other cDNA microarray studies have shown that hepsin is one of the highly over expressed genes in prostate cancer tissue compared with nonmalignant and benign prostatic hyperplasia tissue. We quantitatively analyzed hepsin gene expression with real-time polymerase chain reaction and calculated its relationships with clinicopathological parameters in a large cohort of samples.Materials and Methods: Matched prostate tissue samples from the cancerous and noncancerous parts of the same prostates were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
79
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 16 publications
9
79
1
Order By: Relevance
“…The marked elevation of hepsin in malignant prostate tissues and correlation with increasing Gleason score were in agreement with other data from microarray analyses and real-time PCR studies (Dhanasekaran et al, 2001;Stamey et al, 2001;Ernst et al, 2002;Chen et al, 2003;Riddick et al, 2003;Stephan et al, 2004). The functional importance of hepsin has been shown by its overexpression in a transgenic mouse model of prostate tumorigenesis, which led to basement membrane disorganisation and enhanced metastasis (Klezovitch et al, 2004).…”
Section: Serine Proteases and Inhibitorssupporting
confidence: 76%
“…The marked elevation of hepsin in malignant prostate tissues and correlation with increasing Gleason score were in agreement with other data from microarray analyses and real-time PCR studies (Dhanasekaran et al, 2001;Stamey et al, 2001;Ernst et al, 2002;Chen et al, 2003;Riddick et al, 2003;Stephan et al, 2004). The functional importance of hepsin has been shown by its overexpression in a transgenic mouse model of prostate tumorigenesis, which led to basement membrane disorganisation and enhanced metastasis (Klezovitch et al, 2004).…”
Section: Serine Proteases and Inhibitorssupporting
confidence: 76%
“…Hepsin RNA levels were found to be low in normal prostate and benign hyperplasia but strongly increased in prostate carcinoma, particularly in advanced stages (8 -10). Hepsin protein staining with a monoclonal anti-hepsin antibody showed that hepsin expression was highest at sites of bone metastasis and in late stage primary tumors (12), which is consistent with the finding that increased hepsin RNA levels correlated with higher Gleason grades and tumor progression (7)(8)(9)(10)13). In contrast, using a different antibody Dhanasekaran et al (6) found the strongest hepsin expression in high grade prostate intraneoplastic lesions and lower expression in primary carcinoma and in metastatic lesions.…”
supporting
confidence: 76%
“…In this study, we establish that Ln-332, an important basement membrane component that is apparently down-regulated in human prostate cancer (13)(14)(15)(16), is cleaved by hepsin, a serine protease that is overexpressed in more than 90% of human prostate cancer cases (36). In this report, the experimental evidence that hepsin proteolytically cleaves the Ln-332 ␤3 chain is as follows: 1) treatment of purified Ln-332 with catalytically active hepsin produces an ϳ100-kDa fragment both in a time-and dose-dependent fashion; 2) production of this fragment is abolished by KD1, a specific inhibitor of hepsin; 3) catalytically inactive EGR-hepsin does not promote cleavage; 4) the ϳ100-kDa fragment reacts by Western blot with antibodies against the C terminus of the ␤3 chain; and 5) the sequences of peptides from the ϳ100 kDa band, determined by mass spectrometry, are identical to peptides from the C-terminal region of the rat Ln-332 ␤3 chain.…”
Section: Discussionmentioning
confidence: 99%
“…Loss or down-regulation of various tumor suppressor genes (30,31), as well as up-regulation or overexpression of various genes, has been reported (32)(33)(34). One of the genes found to be up-regulated in more than 90% of human prostate cancer cases is the cell surface protease, hepsin (35,36). Recently, a prostate cancer mouse model demonstrated that hepsin overexpression causes disorganization of BM and promotes prostate cancer progression and metastasis (37).…”
mentioning
confidence: 99%